Factores determinantes para la implementación de prácticas de Responsabilidad Social empresarial en las PYMES del sector industrial del distrito de Tarapoto – 2014 - Fernández Wam, Marcy E. (2014)
The present study aims to explore the different factors that make up the Corporate Social responsibility in order to ascertain the degree of implementation of this management style between small and medium-sized enterprises (SMEs) in the industrial-manufacturero sector of the District of Tarapoto in the Peruvian region of San Martin. In this context of analysis, evaluated the five factors of CSR for SMEs proposed by Jenkins (2006): leadership of the owner/manager, style of management, organizational culture, promotion, and tools and methodologies of CSR management. To this end, a survey was applied to 95 industrial-manufacturero SMEs in Tarapoto district, found that of the five factors analyzed only one of them is practiced by more than half of those. While individual SMEs might have less margin of action compared to large firms which are traditionally the most important references in the field of CSR, taken together those are 14 times higher in number than these; Hence the importance of extending the practice of CSR to the whole of Peruvian companies, since this style of management in the long run is a factor for the improvement of their competitiveness, strengthening its business sustainability and also benefiting the whole of society.